A look at the trajectory and scientific contributions of the archaeologist Luis Hurtado de Mendoza - Peytrequín-Gómez, Jeffrey (2023)
This text discusses the fundamental contributions of the scientific work of a Peruvian archaeologist, who has been based in Costa Rica since the early 1980s and whose professional career unfolded in this country, making great contributions to the field of this discipline: Dr. Luis Hurtado de Mendoza. For this purpose, the author's extensive available literature was analyzed in terms of the topics addressed and their investigative scope; at the same time, interviews were conducted to verify certain contextual data. The results reveal the deployment of thematic pillars covered by this professional, such as the foray into transdisciplinary work, the innovative use of specialized techniques, the multi-scalar approach to different archaeological sites, including Guayabo de Turrialba, and the management of resources (natural and cultural) on a regional scale. Not to mention his impact and experience in teaching at various national and international higher education centers, but primarily at the University of Costa Rica in the early 1980s, where he effectively integrated research with teaching and social action, as well as his performance as a prominent archaeologist at the Costa Rican Institute of Electricity in the first two decades of the 21st century, establishing an exemplary cultural management model.